Increasing Access to Mental Health Supports for 18- to 25-Year-Old Indigenous Youth With the JoyPop Mobile Mental Health App: Study Protocol for a Randomized Controlled Trial. - MacIsaac, Angela; Neufeld, Teagan; Malik, Ishaq; Toombs, Elaine; Olthuis, Janine V; Schmidt, Fred; Dunning, Crystal; Stasiuk, Kristine; Bobinski, Tina; Ohinmaa, Arto; Stewart, Sherry H; Newton, Amanda S; et al. (JMIR Research Protocols, 2025)
Transitional-aged youth have a high burden of mental health difficulties in Canada, with Indigenous youth, in particular, experiencing additional circumstances that challenge their well-being. Mobile health (mHealth) approaches hold promise for supporting individuals in areas with less access to services such as Northern Ontario.